(untitled) (Academia Journal of Medicine, 2025)
Objective: To obtain a comprehensive understanding of the mentorship programs in Aga Khan University Medical College (AKU-MC) and Aga Khan University School of Nursing and Midwifery (AKU-SONAM) by the framework of Program Inputs, activities, followed by triangulation of results. Design: Exploratory study Setting: AKU-MC and AKU SONAMParticipants: mentors, mentees, administrators, and leadership from both entities of the university.Data collection comprised of in-depth interviews (IDIs) focus group discussions (FGDs with administrators and leadership Primary outcome: Comprehensive understanding of the mentorship programs in AKU-MC and AKU-SONAM by the framework of Program Inputs, activities, followed by triangulation of results. Data collection comprised of in-depth interviews (IDIs) focus group discussions (FGDs). Triangulation was applied at the level of entities in i) data collection methods; FGD, and document review, ii) participants; mentors, mentees, administrators and leadership, iii) response from investigators; researcher and supervisory team to enhance the rigor of the study. Results: All the participants from both entities agreed that mentorship programs transferred knowledge and skills, enhanced relationships and facilitated networking. A work-driven and Dyad mentorship model was accredited by mentors, mentees, at AKU-MC and AKU-SONAM respectively. Mentorship committees from both entities oversaw mentor and mentee enrolments, matching, and monitoring of activities The constancy of mentor-mentee meeting frequency, and lack of a structured feedback mechanism were identified as challenges. The significance of recognition, rewards, opportunities for higher qualifications and institutional recognition was suggested by all participants. All Mentors and mentees recommended departmental collaborations and networking for meaningful outcomes.Conclusion: The exploration of context of both mentorship programs revealed that financial and logistic resources of both programs need to be amplified. Mentees were given a choice for selection of mentors for pairing however monitoring of activities may be overcome by selecting appropriate mentors and mentees, practical matching for work relationships, and monitoring successful outcome.